Organic-Inorganic Hybrid Materials II - García-Martínez, Jesús-María; Collar, Emilia P. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Let us introduce this new reprint published by MDPI. This volume is the second part of a previous one devoted to Organic-Inorganic Hybrid Materials, published by MDPI in 2021. As expected, these unique ten contributions fully agree with the definition of hybrid material as per the IUPAC (International Union of Pure and Applied Chemistry) recommendations, defining hybrid materials as the composed of an intimate mixture of inorganic or both types of components interpenetrating scales of less than one micron. Therefore, the reader may deduce that this definition offers many approximations to investigate in the field. Orrganic-inorganic materials are multi-component systems with at least one of their organic (the polymer) or inorganic components in the nano-metric size domain, which confers the material as a whole greatly enhanced properties respecting the constitutive parts in isolation. The works compiled in this volume are at the forefront of Organic-Inorganic Hybrid material research. So, these ten new articles would provide information and inspiration for future applications in this fantastic and fascinating scientific field.